Frequency of Red Cell Alloantibodies in Pregnant Women of North West Pakistan - Maria Shafiq , Ayesha Noor , Amer Siddiq (Journal of Islamic International Medical College, 2017)
Objective: The objective of this study was to determine the frequency of red cell alloantibodies in pregnant women of North West Pakistan. Study Design: It was a descriptive study. Place and Duration of Study. This study was conducted in one year November 2012 to October 2013 at the Haematology Department, Army Medical College, National University of Sciences and Technology (NUST) in collaboration with Department of Gynaecology and Obstetrics, Military Hospital, Rawalpindi. Materials and Methods: A total of 600 samples were studied and it was a non probability convenience sampling. Pregnant females of any age, parity and gestational age were included in the study and women with known autoimmune diseases (SLE, Rheumatoid Arthritis) were excluded. Data was collected through specifically designed proforma and was analysed by using SPSS version 20. Descriptive statistics were used to describe the data. Frequency and percentages were calculated for qualitative variables like blood group and alloantibodies. Mean and standard deviation were calculated for quantitative variables like age, gestational age and parity. Chi-square test was applied to find an association between all categorical variables. p-value <0.05 was considered significant. Results: The frequency of alloantibodies in pregnant women in this study was 0.5% (3/600). Prevalence of alloimmunization specifically in Rh- negative blood group was 5.5% (3/54). All the antibodies detected were anti-D antibodies. Conclusion: Rh D antibodies are the only frequent antibodies in majority of pregnant women with Rh negative blood group. So the practice of routine antenatal antibody screening for every pregnant woman should be avoided.